Image steganography - Jeniffer, Chegaram (2012)
The Internet as a whole does not use secure links,thus information in transit may be vulnerable to interception as well.The important of reducing a chance of the information being detected during the transmission is being an issue now days.Some solution to be discussed is how to passing information in a manner that the very existence of the message is unknown in order to repel attention of the potential attacker.Besides hiding data for confidentiality, this approach of information hiding can be extended to copyright protection for digital media.In this research,we clarify what steganography is,the definition,the importance as well as the technique used in implementing steganography. We focus on the Least Significant Bit (LSB) technique in hiding messages in an image.The system enhanced the LSB technique by randomly dispersing the bits of the message in the image and thus making it harder for unauthorized people to extract the original message.